Capacity Benefit Margin (CBM) assessment incorporating tie-line reliability - Nurulazmi, Abd Rahman; Muhammad Murtadha, Othman; Ismail, Musirin; Azah, Mohamed; Aini, Hussain (Institute of Electrical and Electronics Engineers (IEEE), 2011)
Link to publisher's homepage at http://ieeexplore.ieee.org/